Research on Single Tube Inverter Wireless Power Supply System for LED Lamp Inroadway - WANG Songbai; WANG Chunfang; YUE Rui; LI Dan (Journal of Harbin University of Science and Technology)
In view of the inconvenient replacement of lamps and existing safety problems when using wired way to supply power to LED lamps in the roadway, this paper focuses on a wireless power supply device for LED lamps in the roadway. In order to realize noncontact power supply for LED lamps in roadway, this paper designs a single tube inverter wireless power supply circuit. In this paper, based on the mutual inductance equivalent model, the working mode of the single tube equivalent circuit is analyzed in detail. The realization of voltage gain and circuit soft switch is analyzed in detail. Finally, the constant current characteristic of single transistor inverter circuit is verified by experiments.